Extraction, Toxicity Assay and Identification of Active Compounds of Red Algae (Eucheuma cottonii) from Sumenep Madura - Afif, Sholeh; Fasya, Ahmad Ghanaim; Ningsih, Rachmawati (ALCHEMY, 2015)
Extraction, Toxicity Assay and Identification ofActive Compounds of Red Algae Extract (Eucheuma cottonii) from Tanjung Sumenep Madura was analysed. Extraction of active compound was conducted by maceration method using methanol as a solvent. The methanol extract was hydrolyzed with HCl 2 N. The result was partitioned using five solvents (1-butanol, ethyl acetate, chloroform, petroleum ether and n-hexane). Toxicity level was determined by Brine Shrimp Lethality Test (BSLT). The identification of the active compound was analyzed by phytochemical test, qualitatively. The result showed that the 1-butanol is the best solvent to extract active compounds of red algae E. Cottonii in partition process. 1-Butanol fraction gives the highest activity of toxicity with LC5070,32 ppm. LC50 value for ethyl acetate, chloroform, petroleum ether and n-hexane was 143,43; 194,40; 195,28; 303,66; and 634,97 ppm, respectively. Identification of active compounds indicated that 1-butanol fraction contains steroids and alkaloids. Keywords: Eucheuma cottonii, extraction, Brine Shrimp Lethality Test, phythochemical